VALIDITY OF PERFORMANCE ASSESSMENT OF PRIMARY CLASS TEACHERS - Khurinisa Karimovna Qarshiboyeva (American Journals, 2023)
The article analyzes the issue of the need to evaluate the work of primary school teachers.
Keywords: Knowledge, teacher education skills assessment activities.